Technology, Employment and Social Welfare: technological training as an element of inclusion - Pérez Gázquez, Isabel María (Sociología del Trabajo, 2022)
The irruption of robotics and artificial intelligence in the workplace will mean a new paradigm in relation to employment, occupational polarization and technological gap, whose effects will extend beyond this area and will reach the Welfare State and its financial sustainability. That is why it is necessary to implement actions and measures based on a principle of social responsibility and a fair balance of benefits, which takes into account that technological training of workers becomes a key element of socio-labor inclusion or exclusion and sustainability of the Social Security system.
Keywords: technology; employment; gap; balance; training